2018
DOI: 10.1187/cbe.17-08-0169
|View full text |Cite
|
Sign up to set email alerts
|

Energy Connections and Misconnections across Chemistry and Biology

Abstract: To inform future interdisciplinary course reform, undergraduate students coenrolled in introductory chemistry and cell and molecular biology were interviewed regarding their perceptions of the integration of energy both within and across the disciplines and how they attempted to accommodate and reconcile different disciplinary approaches to energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 87 publications
(131 reference statements)
1
49
0
Order By: Relevance
“…Their schema for what information is relevant in a biology class is different for what information is relevant in a chemistry class. Kohn et al (2018) found that students felt energy was a central concept in their chemistry classes, but not their biology classes. They therefore tended to discount energy concepts in their biology classes.…”
Section: An Overview Of Cognitive Processes In Transfermentioning
confidence: 97%
See 2 more Smart Citations
“…Their schema for what information is relevant in a biology class is different for what information is relevant in a chemistry class. Kohn et al (2018) found that students felt energy was a central concept in their chemistry classes, but not their biology classes. They therefore tended to discount energy concepts in their biology classes.…”
Section: An Overview Of Cognitive Processes In Transfermentioning
confidence: 97%
“…Students' ability to recognize that a previously learned concept applies in a new context depends on their attentional processes as well as their familiarity with, and recognition memory of, the concept. For example, energy is a central concept in physics, chemistry, and biology (see Kohn et al, 2018). Students in a biology class, however, may fail to transfer their understanding of energy as discussed in the chemistry class, simply because they were struggling to pay attention during their biology class.…”
Section: An Overview Of Cognitive Processes In Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…And yet, even without instructional or curricular supports, these students not only made substantive connections between their course work (Appendix D in the Supplemental Material), but nine students converged on a coherent, causal relationship (i.e., structure determines properties, which determine function; Appendix F in the Supplemental Material). This is particularly notable given the difficulty these same students had describing connections between B1 and GC1/GC2 regarding energy ( Kohn et al ., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The NGSS emphasize the development of a coherent understanding of energy changes across different scales and disciplinary contexts, treating all energy as either energy of motion (kinetic energy) or energy stored in fields (potential energy). Researchers in the fields of physics and chemistry education research have similarly expressed a need for interdisciplinary collaboration in the investigation of student understanding of energy as well as in the development of curricula to support student learning [11][12][13].…”
Section: Introductionmentioning
confidence: 99%